1983
DOI: 10.1016/0014-5793(83)80893-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a 167 basepair chromatosome containing a partially digested histone H5

Abstract: A test has been made of the proposal that protection of the 167 basepair DNA length in the 'chromatosome' is due only to the central globular domain of the lysine-rich histones. Chicken erythrocyte chromatin was treated with trypsin to leave only the limit peptide from histones HI and H5. Nucleosome monomers were then isolated on sucrose gradients following micrococcal nuclease digestion and were found to contain the 167 basepair DNA band as in intact chromatin. The presence of the limit peptide from H5 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Since MNase digestion experiments show that the tails of H5 do not affect the interactions between the globular domain and the nucleosome (Allan et al, 1980; Puigdomenech et al, 1983) and the globular domain in complex with the nucleosome has been used as a model for the chromatosome in earlier studies (Allan et al, 1980; Zhou et al, 1998), we reconstituted the globular domain of H5 (H5 22-98 ) in complex with the nucleosome for structural determination. The nucleosome contains 167 bp DNA centered with the 147 bp ‘601’ positioning sequence (Dorigo et al, 2004; Thastrom et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MNase digestion experiments show that the tails of H5 do not affect the interactions between the globular domain and the nucleosome (Allan et al, 1980; Puigdomenech et al, 1983) and the globular domain in complex with the nucleosome has been used as a model for the chromatosome in earlier studies (Allan et al, 1980; Zhou et al, 1998), we reconstituted the globular domain of H5 (H5 22-98 ) in complex with the nucleosome for structural determination. The nucleosome contains 167 bp DNA centered with the 147 bp ‘601’ positioning sequence (Dorigo et al, 2004; Thastrom et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Either the full-length linker histone H5 or the globular domain (H5 24-98 ) alone can protect the same linker DNA in the native chromatin against micrococcal nuclease (MNase) digestion (Allan et al, 1980; Puigdomenech et al, 1983). Earlier studies of nucleosome recognition by linker histones have focused mainly on how the globular domain of H5 binds to the nucleosome (Allan et al, 1980; Cui and Zhurkin, 2009; Fan and Roberts, 2006; Zhou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Either the full-length linker histone H5 or GH5 alone can protect the same native chromatin linker DNA from micrococcal nuclease digestion [23,39]. Recently, we combined X-ray crystallography and NMR to investigate the structural mechanism of nucleosome recognition by GH5 and found that it binds to the nucleosome on the dyad [40].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although the C-terminal tail determines the organization of higher-order chromatin structures (17,23) and the binding geometry of the linker DNA (17,18) it does not appear to affect the LH positioning around the dyad (17). Moreover, the full length LH and the isolated globular domain protect the same L-DNA from micrococcal nuclease digestion (24), indicating that the globular domain determines the binding geometry, whereas the C-terminal tail further refines the interaction with the linker DNA. H5 is an avian LH that differs in sequence from mammalian LH isoforms, but shares most similarity with human H1.0, which is mostly found in terminally differentiated cells (see sequence alignment in Supplementary Data).…”
Section: Introductionmentioning
confidence: 99%